Pelatihan Perhitungan Harga Pokok Produksi (HPP) dan Penyusunan Laporan Laba Rugi Bagi Komunitas UMKM di Provinsi Lampung - Hasnawati, Hasnawati; Wahyuni, Ika; Lestari, Ayu; Dewi, R. Rosiyana; Ariani, Marieta (Empowerment, 2023)
The performance of a business can be seen from the income statement. To be able to calculate the profit or loss of a business, the calculation of the cost of production (HPP) is crucial. An inaccurate HPP calculation will result in an inaccurate pricing as well. If it turns out that the price set is too high to be able to cover the cost of production which is too high, it can have an impact on sales volume where the business can be unable to compete in the market. The UMKM community under the guidance of Bina UMKM Indonesia or Indonesia Small And Medium Enterprises Development (ISMED) is currently having difficulty calculating HPP and preparing their financial reports due to their limited knowledge. This prompted the DIII Tax Accounting Study Program, Faculty of Economics and Business, Trisakti University, to work together with the ISMED community to organize a Community Service Program (PKM) by providing Training Results for Calculation of Cost of Production (HPP) and preparation of financial reports. The results of the PKM activities show: 1) there is an increase in knowledge about calculating HPP and preparing financial reports from the training participants; 2) ongoing training is needed so that the trainees are able to calculate HPP and prepare financial reports independently. Kinerja sebuah usaha dapat dilihat dari laporan laba rugi. Untuk dapat menghitung laba atau rugi sebuah usaha, penghitungan harga pokok produksi (HPP) merupakan hal yang krusial. Penghitungan HPP yang kurang tepat, akan berdampak pada penetapan harga yang kurang tepat juga. Jika ternyata harga yang ditetapkan terlalu tinggi untuk dapat menutup harga pokok produksi terlalu tinggi, bisa berdampak pada volume penjualan dimana usaha tersebut bisa saja kalah bersaing di pasaran. Komunitas UMKM yang berada dibawah binaan Bina UMKM Indonesia atau Indonesia Small And Medium Enterprises Development (ISMED) pada saat ini masih kesulitan dalam menghitung HPP dan Menyusun laporan keuangan mereka dikarenakan keterbatasan pengetahuan yang dimiliki. Hal ini mendorong Program Studi DIII Akuntansi Perpajakan, Fakultas Ekonomi dan Bisnis, Universitas Trisakti, bekerja sama dengan komunitas ISMED untuk menyelenggarakan program Pengabdian Kepada Masyarakat (PKM) dengan memberikan Hasil pelatihan Perhitungan Harga Pokok Produksi (HPP) dan penyusunan laporan keuangan.  Hasil kegiatan PKM menunjukkan: 1) adanya peningkatan pengetahuan tentang penghitungan HPP dan pembuatan laporan keuangan dari para peserta pelatihan; 2) dibutuhkan pelatihan berkelanjutan agar para peserta pelatihan mampu menghitung HPP dan Menyusun laporan keuangan secara mandiri.